Responsibility and Legal Protection of The Parties in Electronic Business Transactions - Anwar Sadat (IHSA Institute, 2021)
The internet brings a lot of changes to every human life, the presence of the internet is widely used as a source of information and to improve the standard of human life, one of the most appropriate business fields, through the internet is to create electronic transactions or e-commerce. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that electronic business or business transactions have been of great interest to all levels of Indonesian society, for example by shopping online, paying taxes, and maybe any purchasing activity can be done. through the e-commerce service, but in the process of implementing the electronic system it seems that it already has a proper legal basis, the government itself through government regulations has issued an ITE Law, which will regulate all forms of buying and selling transactions with the following terms and conditions. certain provisions, this is based on avoiding all forms of irregularities and fraud through the e-commerce service, in addition to the presence of the Law to be able to improve the quality of e-commerce system trading among the Indonesian people.